Molecular taxonomy via DNA barcodes for species identification in selected genera of Fabaceae - Wardani, I Gusti Ayu Kusuma; Amandita, Fitri Yola; Moura, Carina Carneiro de Melo; Gailing, Oliver; Siregar, Iskandar Z (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2022)
Fabaceae is an invaluable plant family with considerable ecological and economic importances for example as food sources, bio-fertilizer, and medicinal plants. However, Fabaceae has been overexploited in Indonesia and several species belong to this family are critically endangered. Due to morphological similarity, rapid and accurate identification of Fabaceae species is essential to support its conservation efforts. Nowadays, species identification through DNA barcoding has become an effective taxonomic classification tool. This study was aimed to evaluate the effectiveness of chloroplast markers, matK and rbcL and the combination (matK+rbcL), as DNA barcodes for the identification of seleted genera in Fabaceae. The result showed that matK+rbcL and matK had the highest level of identification (90% and 82.05%) of the investigated genera, respectively. Additionally, matK had the highest mean of interspesific distance (0.134) and intraspecific distance (0.003). The combined barcode matK+rbcL had the highest correct identification rate when comparing the morphological with molecular identification. Furthermore, the best phylogenetic tree was obtained using Neighbor Joining method. Based on the overall performance, matK and matK+rbcL were the best barcodes for the selected genera in this study.